Simmel’s Law of the Individual: A Relational Idea of Culture - Amat, Matthieu (Simmel Studies)

(untitled) (Georg Simmel Gesellschaft, 2017)
I propose to read Simmel’s developments on the law of the individual as an attempt to solve the problem of modern culture, that is the increasing discrepancy between life and objective mind. I understand the law of the individual as a regulative idea of culture (in the sense of Bildung), which is, at the same time, relational and individual: as an ideal of the most fruitful relation and synthesis between individual life and objective formations of culture.